2018
DOI: 10.5539/elt.v11n7p163
|View full text |Cite
|
Sign up to set email alerts
|

A Health-Check of Communicative Language Teaching (CLT) in Rural Primary Schools of Bangladesh

Abstract: Bangladesh ELT situation has been deteriorating for the last four decades. Regional and national projects including ELTIP and EIA proved to be futile in improving this situation, especially, in the Bangladesh rural primary schools with almost 0% properly trained English teachers to implement the current CLT curriculum. This article investigates the on-going poor health-status of CLT at randomly selected schools of northern Bangladesh through delving into the research gaps linked with the ELT practitioners’ own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Nonetheless, it was impossible to overlook that 78 (25.6%) were neutral and 8 (2.6%) disagreed with the statement. Similar circumstances occurred across several studies whereby it was found that CEFR teachers were not given adequate training, leading to misconceptions about CLT application (Hoque et al, 2018& Nuby, 2019. Furthermore, item B4 (I look positively on the use of CLT approach to replace traditional methods like memorisation and drillings in teaching CEFR speaking lessons) revealed positive attitudes of the respondents, which 145 (47.5%) strongly agreed and 102 (33.4%) agreed on the use of CLT approach as a suitable teaching method which contradicted the findings of a study which claimed that ESL teachers tended to rely on old-school techniques such as memorisation, drilling and translation (Alghamdi, 2021).…”
Section: Esl Primary Teachers' Readiness For the Use Of The Clt Appro...supporting
confidence: 53%
See 1 more Smart Citation
“…Nonetheless, it was impossible to overlook that 78 (25.6%) were neutral and 8 (2.6%) disagreed with the statement. Similar circumstances occurred across several studies whereby it was found that CEFR teachers were not given adequate training, leading to misconceptions about CLT application (Hoque et al, 2018& Nuby, 2019. Furthermore, item B4 (I look positively on the use of CLT approach to replace traditional methods like memorisation and drillings in teaching CEFR speaking lessons) revealed positive attitudes of the respondents, which 145 (47.5%) strongly agreed and 102 (33.4%) agreed on the use of CLT approach as a suitable teaching method which contradicted the findings of a study which claimed that ESL teachers tended to rely on old-school techniques such as memorisation, drilling and translation (Alghamdi, 2021).…”
Section: Esl Primary Teachers' Readiness For the Use Of The Clt Appro...supporting
confidence: 53%
“…Students living in rural communities are often deprived of mastering English because of their poor socio-economic status and relatively low school attendance (Hoque et al, 2018;Nuby et al, 2019). Meanwhile, many struggles to switch their mother tongue to English in daily communication as they fail to comprehend the meanings and necessities of speaking in English (Khoja and Mohapatra, 2017).…”
Section: Challenges Faced Throughout Clt Implementationmentioning
confidence: 99%
“…According to Hoque (2019), different teaching methods can result in different student understandings and learning outcomes. Meanwhile, a qualified teacher is someone who can create learning activity plans.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that the subjects often engaged in activities both in and out of class that helped students improve their pronunciation of the English language. Learning strategies, including self-instruction, naturalistic learning, and self-directed naturalistic learning, are together referred to as "outside-of-class language exposure" (Benson, 2013;Hoque et al, 2018;Hamid et al 2023). What this indicates is that exposure gained through classroom instruction settings alone is insufficient.…”
Section: Literature Reviewmentioning
confidence: 99%